2004
DOI: 10.1139/g03-091
|View full text |Cite
|
Sign up to set email alerts
|

A molecular linkage map of olive (Olea europaeaL.) based on RAPD, microsatellite, and SCAR markers

Abstract: An integrated molecular linkage map of olive (Olea europaea L.) was constructed based on randomly amplified polymorphic DNA (RAPD), sequence characterized amplified region (SCAR), and microsatellite markers using the pseudo-testcross strategy. A mapping population of 104 individuals was generated from an F1 full-sib family of a cross between 'Frantoio' and 'Kalamata'. The hybridity of the mapping population was confirmed by genetic similarity and nonmetric multidimensional scaling. Twenty-three linkage groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 39 publications
6
79
2
2
Order By: Relevance
“…Optical density ratios were evaluated and only good-quality DNA samples were used in polymerase chain reaction (Wu et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Optical density ratios were evaluated and only good-quality DNA samples were used in polymerase chain reaction (Wu et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…This kind of markers was used, together with other DNA-based markers, in the construction of the first olive linkage maps (De la Rosa et al 2004;Wu et al 2004) as well.…”
Section: Random Amplified Polymorphic Dna (Rapds)mentioning
confidence: 99%
“…Many SSRs have been developed in olive and applied with success (Sefc et al, 2000;Carriero et al, 2002;Cipriani et al, 2002;De la Rosa et al, 2003;Sabino Gil et al, 2006). All these characteristics make them ideal markers for applications in analysis of intravariety variability issues (Cipriani et al, 2002;Lopes et al, 2004;Muzzalupo et al, 2009bMuzzalupo et al, , 2010, linkage mapping (Wu et al, 2004) and for characterizing olive germplasm resources (Belaj et al, 2004;Montemurro et al, 2007;Muzzalupo and Perri, 2009). Sarri et al, (2006) confirmed the power of SSR markers in the identification of 118 varieties from different Mediterranean countries to study the genetic diversities of olive varieties.…”
Section: Ssrs (Simple Sequence Repeats)mentioning
confidence: 99%